Analisis Perencanaan PLTS Atap di Gedung H Universitas Pembangunan Panca Budi Medan - Zharfan Asyraf; Rahmaniar; Erpandi Dalimunthe (Faculty of Engineering, Universitas Serambi Mekkah, 2024)
Solar Power Plants (PLTS) are one of the new and renewable energy generation systems (EBT) that are quite promising in the future. In this research, the analysis process for planning a PLTS system as a source of electrical energy in a building is presented. The planned PLTS system will be used to supply the power needs of building H. The power supply capacity is only 60% at the Panca Budi Development University in Medan, but in this case solar panels have been added. The results of the study showed that the PLTS is an off-grid type with the main component specifications needed to supply power to the building, namely 151 solar panels with a capacity of 100 WP, a 46,000 W inverter, and 80 12V 100 Ah Lithium-ion batteries